2011
DOI: 10.1007/s13197-011-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Processing, food applications and safety of aloe vera products: a review

Abstract: Aloe vera is used for vigor, wellness and medicinal purposes since rigvedic times. Health benefits of aloe vera include its application in wound healing, treating burns, minimizing frost bite damage, protection against skin damage from x-rays, lung cancer, intestinal problems, increasing high density lipoprotein (HDL), reducing low density lipoprotein (LDL), reducing blood sugar in diabetics, fighting acquired immune deficiency syndrome (AIDS), allergies and improving immune system. Phytochemistry of aloe vera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(172 citation statements)
references
References 31 publications
2
157
0
13
Order By: Relevance
“…However, only limited data are available on the safety of Aloe vera supplements leaving this issue controversial and uncertain. Few reports have even shown that aloe leaf extract can itself exert some carcinogenic activity (Ahlawat & Khatkar, 2011;Boudreau et al, 2013). Aloin and aloe emodin were found in roots and petioles of Rheum rhaponticum L. (Polygonaceae) (dietary rhubarb) cultivated in Estonia, but not mentioned in folk medicine as the anticancer herbal remedy (Püssa et al, 2009).…”
Section: Herbsmentioning
confidence: 99%
“…However, only limited data are available on the safety of Aloe vera supplements leaving this issue controversial and uncertain. Few reports have even shown that aloe leaf extract can itself exert some carcinogenic activity (Ahlawat & Khatkar, 2011;Boudreau et al, 2013). Aloin and aloe emodin were found in roots and petioles of Rheum rhaponticum L. (Polygonaceae) (dietary rhubarb) cultivated in Estonia, but not mentioned in folk medicine as the anticancer herbal remedy (Püssa et al, 2009).…”
Section: Herbsmentioning
confidence: 99%
“…Now, the processing of Aloe vera gel, derived from the leaf pulp of the plant, has become a big industry worldwide due to application in food industry. Aloe vera gel processed either by traditional hand filleting and/or whole leaf process can be reduced to powder form which improves shelf-life compared to liquid products and eliminate the cost of transport and storage (Ahlawat and Khatkar 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that the Aloe vera polysaccharides (if the active components) in some formulations are not stable, throughout processing/storage where degradation occurs due to heat, acid or enzymes (53). Hence, it might be that processing of such materials should be standardised to preserve the natural biological activities (126,127). The compositional variations among commercial Aloe vera products have been reported by Bozzi et al (128) who studied the authenticity of commercial Aloe vera gel powders from several leading suppliers.…”
Section: Applied Radiationmentioning
confidence: 97%